2007
DOI: 10.1002/ijc.22617
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of CD4+CD25+ human regulatory T cells in vivo: Kinetics of Treg depletion and alterations in immune functions in vivo and in vitro

Abstract: The aim of this study was to investigate whether depletion of CD4 1 CD251 regulatory T cells (Treg) from melanoma patients affects immune responses against tumors. By application of recombinant IL-2-diphteria toxin fusion protein, also known as ONTAK, we were able to significantly reduce the frequency of Treg in peripheral blood, whereas other cell populations remained unaffected. The reduction of Treg started immediately after the first bolus of ONTAK with a dose of 5 lg ONTAK per kg bodyweight and lasted for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
155
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(161 citation statements)
references
References 26 publications
3
155
2
1
Order By: Relevance
“…Diftitox administration in advanced renal cell carcinoma (RCC) patients before dendritic cell vaccination resulted in a reduction in the peripheral Tregs and Treg-mediated immunosuppression. This effect on solid tumours was further corroborated in melanoma patients for whom enhanced antigen-specific CD8 Tcell activity was seen (Mahnke et al, 2007). However, a study evaluating the treatment of melanoma patients with diftitox not only failed to show any favourable clinical improvement, but also showed no change in number or suppressive properties of peripheral Tregs .…”
Section: Direct Targeting Of Tregsmentioning
confidence: 83%
“…Diftitox administration in advanced renal cell carcinoma (RCC) patients before dendritic cell vaccination resulted in a reduction in the peripheral Tregs and Treg-mediated immunosuppression. This effect on solid tumours was further corroborated in melanoma patients for whom enhanced antigen-specific CD8 Tcell activity was seen (Mahnke et al, 2007). However, a study evaluating the treatment of melanoma patients with diftitox not only failed to show any favourable clinical improvement, but also showed no change in number or suppressive properties of peripheral Tregs .…”
Section: Direct Targeting Of Tregsmentioning
confidence: 83%
“…Indeed, both MDSCs, which are known as immunosuppressive immature macrophages, and Tregs determine the prognosis of advanced melanoma patients (30). In addition, Mahnke et al reported that Treg depletion by denileukin diftitox (Ontak ® , Eisai Medical Research, Tokyo, Japan) in melanoma patients resulted in the substantial development of antigen-specific CD8 + T cells in vaccinated individuals (31). Another report also suggested that Treg depletion had a significant clinical effect in unresectable stage IV melanoma patients (32).…”
Section: Discussionmentioning
confidence: 99%
“…For Treg depletion in humans, several reagents are employed such as CY [35], the IL-2 DT fusion protein Denileukin diftitox or ONTAK [36][37][38][39], but the degree of Treg depletion is still limited (about 50%). There also exist antibodies directed against the human CD25 molecule, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The present study, together with the above mentioned works by Ganss et al [32] and Hamzah and co-workers [12] would add T cells to the list of cancer treatment modalities that benefit from normalization of the tumor vasculature. However, it remains a major challenge to unravel the cellular and molecular processes involved in re-modeling of the tumor vasculature and the mechanism by which changes in the vasculature regulate T-cell infiltration.For Treg depletion in humans, several reagents are employed such as CY [35], the IL-2 DT fusion protein Denileukin diftitox or ONTAK [36][37][38][39], but the degree of Treg depletion is still limited (about 50%). There also exist antibodies directed against the human CD25 molecule, e.g.…”
mentioning
confidence: 99%